Template-free ultraspray pyrolysis synthesis of N/Fe-doped carbon microspheres for oxygen reduction electrocatalysis1. Issue 37 (7th October 2015) - Marzorati, S.; Vasconcelos, J. M.; Ding, J.; Longhi, M.; Colavita, Paula E.
<x xml:space="preserve">Abstract</x> Starting from low-cost materials and in the absence of nanostructured templates, C-microspheres with N/Fe active sites for ORR were synthesized via a continuous-flow and scalable USP method.